Location-dependent flight cost difference from the lunar surface to an orbital fuel depot and its influence on in situ resource utilisation location selection - Steinert, Sven J.; Zabel, Paul; Quantius, Dominik (Frontiers in Space Technologies, 2024)
With increasing relevance for lunar activities, the location selection for in situ resource utilization (ISRU) facilities is a necessary step to identify the most suitable configuration during mission planning. To raise information about the dominant location dependencies, a scenario was set up where an ISRU product is exported to an orbital depot and mass costs are used for classification.In the selected scenario, Oxygen is produced by an Ilmenite reduction plant and subsequently exported to the Lunar Gateway via an Oxygen-Hydrogen fueled launcher running in a round-trip, refueling Oxygen at the lunar surface and Hydrogen at the Lunar Gateway. It showed that the variations in transport costs can be either entirely avoided or have a recessive influence on the mission's total costs over an extended amount of time, such as 20 years. The identification of the top 10 most optimal locations for various resolutions were only slightly altered under consideration of flight costs compared to only considering the ISRU factors, which concludes the insignificance of flight cost dependencies for the analysed case.